Incidence of Urinary Problems Post Successful Fistula Repair - Tasnim, Nasira; Bangash, Kauser; Amin, Oreekah; Batool, Afsan (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: The aim was to determine the incidence and association of urinary problems post successful fistula repair. Methods: The retrospective analysis was conducted at Maternal Child Health Pakistan Institute of Medical Sciences, Islamabad, and comprised data related to patients having undergone vesicovaginal fistula repair from January 2008 to June 2018. Various modalities were used to determine the underlying cause of these symptoms including patient’s history, examination, ultrasound, urine examination and urodynamic studies. Statistical analysis of the record was done using SPSS 21 software. Results: Among total 318 successful fistulas repair patients, 78 (24.5%) had urinary problems post operatively. Out of these 78, 56.4% had stress incontinence, 41% infection and 2.6% urge incontinence.13.6% of the stress incontinence was due to sphincter weakness. Urge incontinence was found to be due to detrusor instability. These post-operative urinary complaints were significantly associated with the repair of vesicovaginal (31.3%), urethral (23.1%) and vesicouterine (15.7%) fistula compared to those involving ureter(p 0.04). No significant association was found between the incidence of post-operative urinary complaints and previous history of surgical repair, parity, fistula size and duration of fistula. Conclusions: Urinary incontinence after fistula repair requires careful evaluation as the successful repair of a urogenital fistula can correct the fistula defect, but it might not make the patient dry. Moreover, performing further continence surgery may exacerbate the condition in some cases.